Human health risk assessment of polycyclic aromatic hydrocarbons (PAHs) in smoked fish species from markets in Southern Nigeria - Isioma Tongo; Ozekeke Ogbeide; Lawrence Ezemonye (Toxicology Reports, 2017)
Polycyclic Aromatic Hydrocarbons (PAHs) levels in four commonly consumed smoked fish species from markets in Southern Nigeria were assessed to evaluate possible human health risks associated with consumption. Varying levels of PAH congeners were observed in the fish tissues with the highest total concentration of PAHs in Scomber scombrus. High concentrations of benzo(a)pyrene was observed in Clarias gariepinus and Ethmalosa fimbriata with values above the guideline value of 0.05Â mg/kg. The Dietary Daily Intake (DDI) value for total PAHs (âPAHs) was highest for S. scombrus while the DDI value for the total carcinogenic PAHs (âCPAHs) was highest for E. fimbriata. Carcinogenic human health risk assessment using carcinogenic toxic equivalents (TEQ), indicated that consumption of E. fimbriata has a higher potential to cause carcinogenic risks. TEQ values for all the fish species were however, below the estimated screening value (SV) of 3.556Â mg/kg, while the estimated cumulative excess cancer risk (ECR) for E. fimbriata and C. gariepinus and PAH4 index for all the assessed fish species exceeded threshold values indicating potential carcinogenic risk from consumption. Keywords: PAH, Smoked fish, Human health risk, Risk indices